Detection of Antiphospholipid Antibodies by Flow Cytometry: Rapid Detection of Antibody Isotype and Phospholipid Specificity - Stewart, M W; Etches, W S; Russell, A S; Percy, J S; Johnston, C A; Chew, C K; Gordon, P A (Thrombosis and Haemostasis, 1993)
Laboratory diagnosis of antiphospholipid antibodies is important in patients with clinical features of the antiphospholipid syndrome, such as thrombosis and fetal loss. We have developed a novel method for the detection of antiphospholipid antibodies using flow cytometry. Anionic phospholipids cardiolipin, phosphatidylserine and phosphatidylinositol are coated onto polystyrene beads of different sizes, allowing detection and semiquantitation of their respective phospholipid antibody isotypes. The results of the flow cytometric method closely correlate those of the standardised anticardiolipin enzyme-linked immunosorbent assay (ELISA), but the method is quicker and is versatile in its ability to detect IgG, IgM and IgA antibody isotypes at the same time. The method promises to be useful in evaluating the significance of phospholipid specificity and antibody isotypes in patients with the antiphospholipid syndrome.